Trans-fatty acids in Portuguese food products - Casal, Susana (2016)
There is consistent evidence of adverse health effects from industrial trans-fatty acids (TFAs). Several measures to limit TFA intake have already been taken in various countries, but limited information is available in several countries on the actual TFA content in foods. In order to ensure accurate data on intake of TFAs, and to implement adequate measures to reduce their consumption, each country should have an estimate of the TFA content in the overall diet. The objective of this report is to provide updated data on the TFA content in Portuguese foods. It therefore details the results of 268 samples (acquired and analysed between October and December 2013), chosen based on a previous desk review to identify the food groups of higher concern in terms of their TFA content. The TFAs were quantified by gas chromatography after fat extraction. Potential unconformities were also estimated, taking as a basis a maximum limit of 2% TFAs in the fat.